2001
DOI: 10.1093/chromsci/39.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Hydrocortisone in Human Urine Using a High-Performance Liquid Chromatographic-Tandem Mass Spectrometric-Atmospheric-Pressure Chemical Ionization Method

Abstract: In this study, the development and validation of a method of analysis for 11,17,21,-trihydroxypregn-4-ene-3,20-dione (hydrocortisone, cortisol, HC) using high-performance liquid chromatography (HPLC)-tandem mass spectrometry (MS) with atmospheric-pressure chemical ionization (APCI) is reported. This is the first report of the systematic development and validation of an HPLC-MS-MS method for the quantitation of HC in synthetic human urine with a deuterated internal standard. Prior to LC-MS-MS analysis, the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 1 publication
3
11
0
Order By: Relevance
“…In the case of steroids the fragment pattern is very similar to EI or to particle beam spectra of sterols as published by Byskov et al [21]. CID spectra similar to ours have previously been published for 6␤-OH-hydrocortisone and testosterone [22,23]. The fragments of the sterols presented in Figure 1-3 are calculated as described for particle beam spectra of FF-MAS and lanosterol where a side chain fragmentation was observed [21].…”
Section: Discussionsupporting
confidence: 83%
“…In the case of steroids the fragment pattern is very similar to EI or to particle beam spectra of sterols as published by Byskov et al [21]. CID spectra similar to ours have previously been published for 6␤-OH-hydrocortisone and testosterone [22,23]. The fragments of the sterols presented in Figure 1-3 are calculated as described for particle beam spectra of FF-MAS and lanosterol where a side chain fragmentation was observed [21].…”
Section: Discussionsupporting
confidence: 83%
“…However, in the case of tumors producing only small amounts of serotonin, the predictive values of an increased urinary 5-HIAA is low (Meijer, Kema, Volmer, Willemse, & De Vries, 2000). In addition, the concentration of 5-HIAA in urine may be incresead by consumption of foods rich in 5-HT (Nassar, Varshney, Getek, & Cheng, 2001;Patel, Arundell, Parker, & Yeoman, 2005). It has been shown that platelet serotonin is the most sensitive indole marker for the diagnostic of caracinoid tumors, especially those with low serotonin production (Meijer & al., 2000;Kema et al, 2001;Kema et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic methods accurately measure UF, not only reducing the interference for the F quantification, but also allow quantification of the E [13][14][15]. Moreover, liquid chromatography-mass spectrometry (LC-MS), and gas chromatography-mass spectrometry (GC-MS) [15][16][17] have the disadvantage of being expensive and are not available in all laboratories. Liquid chromatography with ultraviolet detection (LC-UV) coupled with solid phase extraction (SPE), to eliminate interfering compounds, is a practical and cheaper technique [18,19].…”
Section: Introductionmentioning
confidence: 99%